Case Report: Recombinant human growth hormone therapy in a patient with spondyloepiphyseal dysplasia, Kondo-Fu type - Chen, Congli; Wu, Jin; Liu, Ying (Frontiers in Pediatrics, 2023)
Background: variants in membrane-bound transcription factor peptidase, site 1(MBTPS1) gene can result in clinically rare spondyloepiphyseal dysplasia of Kondo-fu type (OMIM #618392, SEDKF), Silver-Rusell syndrome, and CAOP (cataract, alopecia, oral mucosal disorder, and psoriasis-like) syndrome. Case presentation: A 6-year-old Chinese male child diagnosed with SEDKF underwent 3 years of growth hormone therapy. Genetic examination revealed two new nonsense variants in MBTPS1 gene on chromosome 16q23-q24 with compound heterozygotes c.1589(exon12)A>G and c.163(exon2)G>A. Conclusion: MBTPS1 gene c.1589(exon12)A>G and c.163(exon2)G>A on chromosome 16q23-q24 is associated with SEDKF. Growth hormone therapy can improve growth retardation in patients with spondyloepiphyseal dysplasia, Kondo-Fu type, yet more cases are required to support this hypothesis.